Desenvolvimento experimental de um motor stirling tipo gama - Cruz, Vinicius Guimarães da (2012)
The current paper develops an experimental Stirling engine Gama type. Different settings of this type of engine are presented (alpha, beta and gamma), along with the Stirling Cycle Definition and the mathematical modeling for each setting. It´s been Proceed a mathematical analysis based on the Stirling Theory, which is the method based upon the isothermical compression and expansion of an ideal gas, put to analysis by a computer software, determining the dependency between the engine s construction and functioning parameters. Bibliography used takes over the main Stirling engine settings and various working conditions, fed by a numerous types of fuels. The experimental part of the paper is assembling of a Stirling engine gamma type containing no regenerator, therefore, having the air as its working fluid, using electrical resistances as heat source, also a water jet at ambiance temperature to cool down the compression and heat exchanger. Engine tests were performed at atmospheric pressure, temperatures from 100 to 600 °C, 100 to 400 rpm rotations. The results are presented in graphics and are questioned.